Daya Saing Sekolah Menengah Kejuruan (SMK) Muhammadiyah dalam Era Revolusi Industri 4.0; Studi pada Sekolah Menengah Kejuruan (SMK) Maritim Muhammadiyah Kendari - Leliy - Kholida; Muallimah Muallimah (Arfannur, 2021)
The competitiveness of vocational schools (vocational) is one of the concerns of many parties with the presence of great changes rapidly due to the industrial revolution 4.0. The big wave created as a result of the 4.0 industrial revolution shook almost all sectors, the impact of which was education the most because this sector was directly related to causality. From existing research and studies, researchers have not found studies that specifically reveal the response of vocational education institutions in dealing with the impact of changes due to the industrial revolution 4.0, regarding the process of building competitiveness (competitiveness) institutionally in vocational schools, especially in Muhammadiyah vocational schools. This research uses a holistic approach to vocational institutions in the process of building competitiveness institutionally to face the impact of changes caused by the industrial revolution 4.0. This research is a microscopic study that focuses on the Muhammadiyah Kendari Vocational High School which was established on July 16, 2018. In this study, there are two formulations of how the Muhammadiyah Kendari Maritime Vocational High School (SMK) responds to changes due to the Industrial revolution 4.0?; and how is the process of building competitiveness carried out by the Muhammadiyah Kendari Maritime Vocational High School (SMK) to be competitive in the era of the industrial revolution 4.0? .research results are: 1. The establishment of this Muhammadiyah Maritime Vocational School is in realizing maritime physics in the form of educational institutions. The Maritime Vocational School of Muhammadiyah Kendari is the only vocational school that provides NKPi’s vocational maritime expertise, and the APHPi-based Muhammadiyah boarding school in Southeast Sulawesi compared to the other four SMK units in Southeast Sulawesi, as well as adding to the maritime treasures throughout Indonesia which there are no more than twelve units of vocational high schools in Muhammadiyah Dikdasmen. 2. The process of building competitiveness in the maritime SMK Muhammadiyah Kendari there are four aspects as follows: a) Learning innovation as a 21st century learning model using WhatsApp (WA) and Facebook (fb). b) SMK Maritim Muhammadiyah Kendari is a form of school collaboration with the University Muhammadiyah Kendari, especially the Faculty of Fisheries and Marine Sciences. Full guidance and support from educators from the Faculty of Fisheries, University of Muhammadiyah Kendari. c) the leadership roles of Mr. Kasman in the Maritime Vocational School of Muhammadiyah Kendari are manifested in the role of carrying out the role as a pioneer focusing on recognizing internal and external conditions, d) The Maritime Vocational School of Muhammadiyah Kendari is the only private vocational school that has the main infrastructure and full property rights, compared to with the four similar vocational schools, the infrastructure facilities are still not standardized. Abstrak Daya saing sekolah kejuruan (vokasi) menjadi salah satu perhatian banyak pihak dengan hadirnya perubahan hebat secara cepat akibat revolusi industri 4.0. Gelombang besar yang tercipta akibat revolusi industri 4.0 ini mengguncang nyaris semua sektor, yang paling terasa dampaknya pendidikan karena sektor ini berhubungan langsung secara kausalitas. Dari penelitian dan kajian-kajian yang telah ada, peneliti belum menemukan kajian yang secara khusus mengungkap respon lembaga-lembaga pendidikan SMK dalam menghadapi dampak perubahan akibat revolusi industri 4.0, tentang proses membangun daya saing (competitiveness) secara kelembagaan SMK, terlebih pada SMK Muhammadiyah. Penelitian ini dengan pendekatan holistik kelembagaan SMK dalam proses membangun daya saing secara kelembagaan menghadapi dampak perubahan yang ditimbulkan revolusi industri 4.0.Penelitian ini merupakan kajian secara mikroskopis yang berfokus pada sekolah Menengah Kejuruan Kemaritiman Muhammadiyah Kendari yang berdiri 16 Juli 2018. Dalam penelitian ini ada dua rumusan Bagaimana Sekolah Menengah Kejuruan (SMK) Kemaritiman Muhammadiyah Kendari merespon perubahan akibat revolusi Industri 4.0?; dan bagaimana proses membangun daya saing yang dilakukan Sekolah Menengah Kejuruan (SMK) Kemaritiman Muhammadiyah Kendari untuk berdaya saing dalam era revolusi industri 4.0?. Hasil penelitian ini menunjukkan bahwasanya 1. Pembentukan SMK Maritim Muhammadiyah ini dalam mewujudkan fisik kemaritiman dalam bentuk lembaga pendidikan. SMK Maritim Muhammadiyah Kendari merupakan satu-satunya SMK yang menyediakan keahlian kemaritiman kejuruan NKPi, dan APHPi yang berbasis Muhammadiyah boarding School di Sulawesi Tenggara dibanding dengan ke-empat unit SMK lainnya di Sulawesi Tenggara, serta menambah khazanah kemaritiman se-Indonesia yang baru ada tidak lebih dua belas unit sekolah menengah kejuruan di Dikdasmen Muhammadiyah. 2. Proses membangun daya saing di SMK maritim Muhammadiyah Kendari ada empat aspek sebagai berikut: a) Inovasi pembelajaran sebagai model pembelajaran abad 21 menggunakan WhatsApp (WA) dan facebook (fb).b) SMK Maritim Muhammadiyah Kendari merupakan bentuk kerja sama sekolah dengan Universitas Muhammadiyah Kendari, khususnya Fakultas Perikanan dan Ilmu Kelautan. Pembinaan dan dukungan penuh dari para pendidik dari fakultas Perikanan Universitas Muhammadiyah Kendari. c) peran-peran kepemimpinan bapak Kasman di SMK Maritim Muhammadiyah Kendari diwujudkan pada peran menjalankan peran sebagai perintis focus mengenali kondisi internal dan eksternal, d) SMK Maritim Muhammadiyah Kendari merupakan satu-satunya SMK swasta yang memiliki sarana prasarana utama dan hak milik penuh, dibandingkan dengan keempat sekolah kejuruan yang serupa masih belum terstandar sarana prasarananya. Kata Kunci: daya saing dan Sekolah Menengah Kejuruan